Cross-border transmission of emergency liquidity - Kick, Thomas; Koetter, Michael; Storz, Manuela (Journal of Banking & Finance, 2020)
We show that emergency liquidity provision by the Federal Reserve transmitted to non-U.S. banking markets. Based on manually collected holding company structures, we identify banks in Germany with access to U.S. facilities. Using detailed interest rate data reported to the German central bank, we compare lending and borrowing rates of banks with and without such access. U.S. liquidity shocks cause a significant decrease in the short-term funding costs of the average German bank with access. This reduction is mitigated for banks with more vulnerable balance sheets prior to the inception of emergency liquidity. We also find a significant pass-through in terms of lower corporate credit rates charged for banks with the lowest pre-crisis leverage, US-dollar funding needs, and liquidity buffers. Spillover effects from U.S. emergency liquidity provision are generally confined to short-term rates.